Microdialysis in awake macaque monkeys for central nervous system pharmacokinetics. Issue 4 (4th December 2018) - Thiollier, Thibaud; Wu, Caisheng; Porras, Gregory; Bezard, Erwan; Li, Qin; Zhang, Jinlan; Contamin, Hugues
Abstract: Background: The brain bioavailability of novel small molecules developed to address central nervous system disease is classically documented through ex vivo or in vivo analyses conducted in rodent models. Data acquired in rodent models are, however, not easily transferrable to human as the pharmacokinetic and pharmacodynamics profiles of the species are quite different. Methods: Using drugs selected for their differential transport across the blood‐brain barrier, we here demonstrate the feasibility of brain microdialysis in normal vigil macaque monkey by measuring brain extracellular fluid bioavailability of carbamazepine, digoxin, oxycodone, and quinidine. Results: All drugs, but digoxin, were found in dialysate samples. Drugs that are substrate of P‐glycoprotein show a difference of bioavailability or brain pharmacokinetic parameters between rodents and primates. Conclusion: Data suggest that brain microdialysis in vigil macaque monkey, the species of choice for classic pharmacokinetic/pharmacodynamics studies could help predicting human brain bioavailability of a small molecule depending on the protein involved in the efflux transport from the brain.